Sleep and Organizational Behavior: Implications for Workplace Productivity and Safety - Pilcher, June J.; Morris, Drew M. (Frontiers in Psychology, 2020)
The interaction between sleep and work-related behaviors influence many aspects of employee performance, safety, and health as well as organizational-level success. Although it is well established that quantity and quality of sleep can affect different types of task performance and personal health, the interactions between sleep habits and organizational behaviors have received much less attention. It is important to examine how sleep habits and workplace behaviors relate and the role of the underlying circadian rhythm on the potential impact of sleep and sleepiness in the workplace. Developing a deeper understanding of how sleep habits and sleepiness impact workers and the organization can help provide the necessary background for human resource management to develop more progressive support networks for employees that benefit both the worker and the organization. Human resources and employees should emphasize the impact of good sleep and sleep habits on organizational and individual productivity and safety.